STUDENTS’ ENGLISH ACHIEVEMENT PROFILE OF SMKN 1 TELUK KERAMAT - Pratamawadi, Yoga; Supardi, Iwan; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research is aimed at knowing the students’ English achievement profile from 2010 - 2014 at SMKN 1 Teluk Keramat, Sekura. The method used in this research is descriptive. Based on the analysis, the mean score ( ) of students’ English national examination (Ujian Nasional/UN) achievement in 2010 was 6.29 with standard deviation (SD) of 1.25. In UN 2011, = 7.2 and SD= 1.28. In UN 2012, = 5.14 and SD= 1.61. In UN 2013, = 5.79 and SD= 1.09; and in UN 2014, = 4.81 and SD= 1.23. In five years, students’ English mean scores ( ) in the national examination in SMKN 1 Teluk Keramat, Sekura was 5.85 with the standard deviation of 1.56. It is concluded that the students’ English achievement profile in SMKN 1 Teluk Keramat, Sekura in the last five years showed an inconsistency trend and tended to show a negative progress.Keywords: Achievement profile, national examination (UN)Abstrak: Penelitian ini bertujuan untuk mengetahui profil pencapaian siswa pada mata pelajaran Bahasa Inggris pada tahun 2010 sampai 2014 pada SMKN 1 Teluk Keramat, Sekura. Metode yang digunakan pada penelitian ini adalah deskriptif. Berdasarkan analisis, nilai rata-rata ( ) pencapaian Bahasa Inggris siswa pada ujian nasional (UN) tahun 2010 adalah 6.29 dengan standar deviasi (SD) 1.25. UN 2011, =7.2 dan SD= 1.28. UN 2012, =5.14 dan SD=1.61. UN 2013, =5.79 dan SD=1.09; dan pada UN 2014, =4.81 dan SD=1.23. Dalam lima tahun terakhir, Nilai rata-rata Bahasa Inggris siswa pada ujian nasional di SMKN 1 Teluk Keramat, Sekura adalah 5.85 dengan standar deviasi 1.56. Dapat disimpulkan bahwa profil pencapaian Bahasa Inggris siswa SMKN 1 Teluk Keramat, Sekura dalam lima tahun terakhir menunjukan inkonsistensi dan cendrung menunjukan adanya penurunan.Kata kunci: Profil pencapaian, ujian nasional (UN)